Health knowledge of adults in Polangui, Albay by Brenda Rosario Ante - Ante, Brenda Rosario 1948- (s.n.], 1974)
The health knowledge of adults in Polangui, Albay was determined in this study. Specifically, this research tested the extent of the health knowledge and the significant differences, if there are any, in the adults' health knowledge due to factors such as sex, age, marital status, occupation, income and educational attainment.